2017
DOI: 10.1155/2017/9056470
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Its Association with Parathyroid Hormone Concentration in Brazilians

Abstract: Vitamins are organic compounds that play a vital role in the control of metabolic processes. The D complex is considered a nutrient with a hormonal action and has an important participation in the constant maintenance of serum and extracellular calcium levels. The present study aims to analyze the results of 105.588 vitamin D (25(OH)D) measurements obtained from a database from a clinical analysis laboratory in Brazil, between the years of 2011 and 2013. The values of 25(OH)D were correlated with age, gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 37 publications
5
22
0
Order By: Relevance
“…Our results revealed the serum iPTH level was negatively correlated with the serum 25(OH)D 3 level when the serum 25(OH)D 3 level was lower than 20 ng/mL. When the serum 25(OH)D 3 level was above 20 ng/mL, then no linear correlation between 25(OH)D 3 and iPTH levels was noted, which was consistent with the results of the study by Martins et al among Brazilians [46]. Matejek et al reported a significant relationship between iPTH and 25(OH)D 3 from the second month of life in healthy preterm newborns and that decreasing the 25(OH)D 3 level was accompanied by increasing iPTH [47].…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed the serum iPTH level was negatively correlated with the serum 25(OH)D 3 level when the serum 25(OH)D 3 level was lower than 20 ng/mL. When the serum 25(OH)D 3 level was above 20 ng/mL, then no linear correlation between 25(OH)D 3 and iPTH levels was noted, which was consistent with the results of the study by Martins et al among Brazilians [46]. Matejek et al reported a significant relationship between iPTH and 25(OH)D 3 from the second month of life in healthy preterm newborns and that decreasing the 25(OH)D 3 level was accompanied by increasing iPTH [47].…”
Section: Discussionsupporting
confidence: 92%
“…A human study in Brazilian population has reported a negative correlation between 25‐hydroxyvitamin D3 and PTH levels . In our study, the levels of calcium were similar between groups.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, Augoulea et al reported that an increase in PTH caused by denosumab therapy was not associated with serum 25(OH) D levels 25. Serum 1,25(OH) 2 D 3 levels are strictly regulated by elevations in PTH26 that are initiated by transient changes in calcium levels as reported previously,27 and there is a negative correlation between 25(OH)D and PTH levels in Brazilians 28. Also, Wintermeyer et al have reviewed and reported that 25(OH)D is metabolized to 1,25(OH) 2 D 3 (calcitriol), which is the biologically active form of vitamin D in the kidney 29.…”
Section: Discussionsupporting
confidence: 52%